El porqué de nuestros diseños : 10 arquitectos explican su obra - Suckle, Abby (CEA, 1984)
Diseño, construcción y arquitectura de:<Erickson, Arthur>; <Pelli, Cesar>; <Kurokawa, Kisho>; <Hertzberger, Herman>; <Johansen, John>; <Maki, Fumihiko>; <McCue, Gerald>; <Rogers, Richard>; <Seidler, Harry>; <Foster, Norman>.